Does Company Size Moderating The Effect of Sustainability Report Disclosure on Performance? - Rosdiana, Yuni; Mulyani, Susi Dwi (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Abstract This study intends to investigate and analyze the effect of sustainability report disclosure on financial performance, the effect of company size on financial performance, and the moderating influence of company size on the relationship between sustainability report disclosure and financial performance. The employed research design is descriptive and associative, with a sample of thirteen LQ 45 companies from 2017 to 2021 that meet the inclusion criteria, selected using purposive sampling. This study utilized secondary data collected from the Indonesia Stock Exchange's (IDX) website-accessible annual reports. According to the study's findings, sustainability report disclosure has a positive impact on financial performance, company size has a positive impact on financial performance, and company size moderates the relationship between sustainability report disclosure and financial performance.